1987
DOI: 10.1177/154079698701200107
|View full text |Cite
|
Sign up to set email alerts
|

Payment Mechanisms for Community Employment: Realities and Recommendations

Abstract: This article describes the payment mechanisms cur rently available to reimburse workers with severe disa bilities for work performed. The advantages and disad vantages of competitive employment at or above mini mum wage, competitive employment below minimum wage, contracted employment through a rehabilitation agency, and self-employment are discussed. In addition, suggestions for utilization and regulatory reform are addressed.Many persons with severe disabilities have had the benefit of an integrated public e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…At the April team meeting, the transition coordinator reported that Keith had been officially hired by the electrical firm the week before, thanks to the efforts of his case worker and employer, who applied for a subminimum wage certilicate from the U.S. Department of Labor. This allowed Keith to be paid a salary that was less than that of other employees, based on his productivity (Hagner, Nisbet, Callahan, & Moseley, 1987;Mcloughlin, Garner, & Callahan, 1987). He was spending 4 full days each week on the job; the fifth day was spent in the community or at home, receiving instruction in nonwork areas such as cooking, self-care, or leisure activities.…”
Section: Step 7: Conduct a Follow-up Of Iiie Itp Goals And Objectivesmentioning
confidence: 99%
“…At the April team meeting, the transition coordinator reported that Keith had been officially hired by the electrical firm the week before, thanks to the efforts of his case worker and employer, who applied for a subminimum wage certilicate from the U.S. Department of Labor. This allowed Keith to be paid a salary that was less than that of other employees, based on his productivity (Hagner, Nisbet, Callahan, & Moseley, 1987;Mcloughlin, Garner, & Callahan, 1987). He was spending 4 full days each week on the job; the fifth day was spent in the community or at home, receiving instruction in nonwork areas such as cooking, self-care, or leisure activities.…”
Section: Step 7: Conduct a Follow-up Of Iiie Itp Goals And Objectivesmentioning
confidence: 99%
“…Since workers with developmental disabilities differ in their abilities to conduct job searches and job interviews, a variety of strategies are necessary along a continuum from minimal to full assistance in this process (McLoughlin, Garner, & Callahan, 1987). Professionals should be familiar with alternative wage payment mechanisms for workers with severe disabilities who cannot meet all the productivity demands of a job (Hagner, Nisbet, Callahan, & Moseley, 1987).…”
Section: Systemic Interventionsmentioning
confidence: 99%